2019
DOI: 10.1159/000501549
|View full text |Cite
|
Sign up to set email alerts
|

Is Blood Urea Concentration an Independent Predictor of Positive Endoscopic Findings in Presumed Upper Gastrointestinal Bleeding?

Abstract: Background: The test characteristics of blood urea concentration in the identification of upper gastrointestinal bleeding (UGIB) or high-risk endoscopic lesions have not been clearly determined. This study aimed to elucidate if urea independently correlates with the presence of positive endoscopic findings in cases of presumed UGIB and understand the diagnostic value of this parameter when assessing a patient with potential UGIB. Methods: A retrospective cohort study was conducted at Hamilton Health Sciences h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 22 publications
1
3
0
Order By: Relevance
“…But mean values of urea in a patient with varices and without varices were 63±45 and 37±24, respectively, showing a statistically significant correlation (p value-0.031). These findings were in concordance with a study done by Chopra et al [16] on blood urea concentration as an independent marker for the prediction of positive endoscopic findings in presumed upper gastrointestinal bleeding showed that urea may be used as a surrogate marker for the prediction of upper gastrointestinal bleed. But when we compared serum urea levels between large varices (Grade III/IV) (Group A) vs Grade I/II/No varices) (Group B), there was no statistically significant difference between the two groups, signifying that urea levels can be used to predict the presence of varices but cannot discriminate between groups with highgrade vs low-grade varices.…”
Section: Discussionsupporting
confidence: 93%
“…But mean values of urea in a patient with varices and without varices were 63±45 and 37±24, respectively, showing a statistically significant correlation (p value-0.031). These findings were in concordance with a study done by Chopra et al [16] on blood urea concentration as an independent marker for the prediction of positive endoscopic findings in presumed upper gastrointestinal bleeding showed that urea may be used as a surrogate marker for the prediction of upper gastrointestinal bleed. But when we compared serum urea levels between large varices (Grade III/IV) (Group A) vs Grade I/II/No varices) (Group B), there was no statistically significant difference between the two groups, signifying that urea levels can be used to predict the presence of varices but cannot discriminate between groups with highgrade vs low-grade varices.…”
Section: Discussionsupporting
confidence: 93%
“…Several studies have shown an association between urea levels and the severity of upper gastrointestinal bleedings. [37][38][39][40] Pathophysiologically, this link can be referred to as a gastrointestinal breakdown of blood components that leads to reabsorption of amino acids which in turn causes a rise of urea, the end product of amino acid metabolism. 40 Furthermore, high urea is a marker for renal hypoperfusion and consequentially an indicator of hypovolemia.…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest that besides renal dysfunction, urea might reflect other factors associated with mortality in patients undergoing TIPS. Several studies have shown an association between urea levels and the severity of upper gastrointestinal bleedings 37–40 . Pathophysiologically, this link can be referred to as a gastrointestinal breakdown of blood components that leads to reabsorption of amino acids which in turn causes a rise of urea, the end product of amino acid metabolism 40 .…”
Section: Discussionmentioning
confidence: 99%
“…In a study in 2020 study reported that urea level was an independent predictor of positive endoscopic findings in upper GI bleeding and that early endoscopic intervention should be considered in patients with elevated urea levels. 7 Some studies have used the BUN/Creatinine ratio as an index to differentiate between upper and lower GI bleeding and have shown that a higher BUN/ Cr ratio is associated with a higher likelihood of upper GI bleeding. 8,9 In cases of ongoing bleeding in any area of the body, a decrease in hemoglobin levels is expected.…”
Section: Introductionmentioning
confidence: 99%